PREFERENSI MUSIK DI KALANGAN REMAJA - Prasetiyo, Ayub (PROMUSIKA, 2013)
The main purpose of this study is to understand the interest trend of music preference among youths as well as to analyse factors that influence the trend. Although qualitative method was used, this study utilized questioner for its data collecting technique. The collected data was analyzed to gather respondents’s point of views and answers concerning music that they like. This study conclude that music interest trend among youth is mostly to popular music. Although the music has taken the highest rank position, its supporters are not only listen to their main preference but also other musical styles. Youths’s tendency to choose popular music have been based on several factors such as, the objective value of the music, the capability of the music to represent conditions that are experienced by them, as well as musical meaning among the youths. Keywords: Music preference, popular music, youths